Analisis Penerapan Fungsi Manajemen Syariah dalam Pengelolaan Administrasi dan Keuangan Kesantrian: (Studi Pondok Pesantren Imam Syafi’i) - Faizal Abdau; Mohamad Maftuh Fauzi (EBISMAN eBisnis Manajemen, 2026)
This study aims to analyze the implementation of sharia management functions in the administration and financial management of student affairs at Imam Syafi’i Islamic Boarding School (Pondok Pesantren Imam Syafi’i) in Brebes. Islamic boarding schools play an important role not only in developing students’ religious knowledge and character but also in managing administrative and financial systems that support educational activities. In the perspective of sharia management, organizational management should be carried out based on the main management functions, namely planning, organizing, actuating, and controlling, while also adhering to Islamic values such as trustworthiness (amanah), transparency, and accountability. This research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation during the PIAWAI Internship Program of the Sharia Management Study Program in 2025. The results show that the administration and financial management of student affairs at Imam Syafi’i Islamic Boarding School have implemented management functions systematically, starting from activity and budget planning, task distribution among student affairs administrators, implementation of administrative processes and financial recording, to supervision and evaluation of financial reports. In addition, the management practices also reflect sharia management principles through the application of trust, accountability, and transparency in managing students’ activity funds. Therefore, the implementation of sharia management functions in administration and financial management contributes to improving the effectiveness of pesantren activities and strengthening governance in Islamic educational institutions.